Response of safflower to different concentrations of Mubkoet Chlorocytide growth regulator - Hussain Ali (College of Education for Pure Sciences, 2005)
This study has dealt with the effect of four different concentrations (0.0 control, 20,40 and 60) ppm of the growth regulator (mepiquat chloride) on the growth and some physiological aspects of safflower under green-house conditions. The main results indicate that the addition of the growth regulator in different concentrations has led to decrease in the height plant, root length , and significant increase in the dry weight of shoots and roots, especially with concentration of (20) and (40) ppm. The spraying of the shoots, has led to increase the relative water content in the plant leaves and decrease the cell membrane stability in comparison with untreated plants, moreover a significant decrease noticed in the concentration of proline especially with concentrations of (20) and (40) ppm and increase in the concentration of chlorophyll b particularly with concentration (60) ppm.